Asociación a sustratos de los erizos regulares (Echinodermata: Echinoidea) en la laguna arrecifal de Isla Verde, Veracruz, México - Celaya-Hernández, E. V. (2008)
Regular sea urchins substrate association (Echinodermata: Echinoidea) on Isla Verde lagoon reef, Veracruz, Mexico. The diversity, abundance, distribution and substrate association of the regular sea urchins found at the South part of Isla Verde lagoon reef, Veracruz, Mexico is presented. Four field sampling trips where made between October, 2000 and October, 2002. One sampling quadrant (23 716 m2) the more representative, where selected in the southwest zone of the lagoon reef, but other sampling sites where choose in order to cover the south part of the reef lagoon. The species found were: Eucidaris tribuloides tribuloides, Diadema antillarum, Centrostephanus longispinus rubicingulus, Echinometra lucunter lucunter, Echinometra viridis, Lytechinus variegatus and Tripneustes ventricosus. The relation analysis between the density of the echinoids species found in the study area and the type of substrate was made using the Canonical Correspondence Analysis (CCA). The substrates types considerate in the analysis where: coral-rocks, rocks, rocks-sand, and sand and Thalassia testudinum. The sand substrate with pieces of shell fragments was omitted from the analysis, since D. antillarum was the only species present in this habitat. During the two sampling climatic seasons the distribution of E. tribuloides tribuloides and C. longispinus rubicingulus was investigated to determine their substrate association on coral-rock and rock. The distribution of D. antillarum, E. lucunter lucunter and E. viridis was mainly associated to coral-rock, rock and sand substrates, while which the distribution of L. variegatus and T. ventricosus was more associated with presence of sea grass. The distribution of sea urchins is associated with the substrate type and their feeding habits which are also intimately linked. The seven species reached their biggest abundance during the raining season. E. lucunter lucunter and D. antillarum are considered in this study as bioindicators of the ecological quality of the coral reef. Rev. Biol. Trop. 56 (Suppl. 3): 281-295. Epub 2009 January 05.